Social harm at the border: the case of Lampedusa - Soliman, Francesca (Routledge studies in criminal justice, borders and citizenship, 2024)
"This book offers a zemiological approach for understanding border control practices, state power, and their social impact. Drawing on an ethnographic study on the borderisation of the Mediterranean island of Lampedusa, it explores border harms from the perspective of the non-migrant community. Social Harm at the Border examines a range of social harms associated with border control, and draws on themes of security, racialised humanitarianism, economic harms, environment, and culture. It explores the ways in which borderisation exercises control over both migrants and non-migrants, ensuring that border communities remain subordinated to the power of institutional actors, and it offers a novel framework with which to illuminate and explain border harms and their generative mechanisms. An accessible and compelling read, this book will appeal to students and scholars of criminology, zemiology, sociology, criminal justice, politics, geography, and those interested in the harms caused by border control practices"--